Analytische, numerische und messtechnische Untersuchung der Dynamik von Fahrzeugkupplungen am Beispiel des Trennproblems - Tikhomolov, Arsenty (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2015)
The clutch systems have a variety of disturbing dynamic phenomena. One of them, the problem of dynamic engagement, firstly is considered by measurement and analytically. Then a 3D-multibody system is created in order to describe the clutch system dynamics. This model is applied for the research of the problem of dynamic engagement, the engagement rattle and the clutch pedal vibrations. To validate the model the simulation results are compared with the experimental results.